ANALYSIS OF FRAUD TRIANGLE FACTORS AND FINANCIAL DISTRESS THAT INFLUENCE FINANCIAL STATEMENT FRAUD IN REAL ESTATE COMPANIES LISTED ON THE IDX - Vahrunnisa Purba; Abdillah Arif Nasution; Narumondang Bulan Siregar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine the influence of fraud triangle factors including financial stability, external pressure, opportunity and rationalization and financial distress on financial statement fraud in Real Estate companies listed on the IDX in 2018 - 2022. The study was conducted based on the 2022 ACFE report that financial statement fraud has the highest average loss of any type of fraud and it is known that the Real Estate industry is the industry that experiences the most average losses from fraud. The sampling technique used was purposive sampling with a sample of 33 companies during 5 years of observation so that the total number of observation samples was 165. The analysis technique used was regression analysis on quantitative data with panel data on Eviews software version 13. The results of the study indicate that opportunity and financial distress have a positive effect on financial statement fraud and rationalization has a negative effect on financial statement fraud. While financial stability and external pressure do not affect financial statement fraud.